2012
DOI: 10.1371/journal.pone.0048371
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound in the Diagnosis of Gallbladder Diseases: A Multi-Center Experience

Abstract: ObjectiveTo assess the usefulness of contrast–enhanced ultrasound (CEUS) in differentiating malignant from benign gallbladder (GB) diseases.MethodsThis study had institutional review board approval. 192 patients with GB diseases from 9 university hospitals were studied. After intravenous bonus injection of a phospholipid-stabilized shell microbubble contrast agent, lesions were scanned with low acoustic power CEUS. A multiple logistic regression analysis was performed to identify diagnostic clues from 17 indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 24 publications
1
67
0
1
Order By: Relevance
“…From eighty-nine clinical studies, sixteen studies fulfilled the inclusion criteria and were included in the metaanalysis [7,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. There were a total of 1673 gallbladder carcinoma cases.…”
Section: Resultsmentioning
confidence: 99%
“…From eighty-nine clinical studies, sixteen studies fulfilled the inclusion criteria and were included in the metaanalysis [7,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. There were a total of 1673 gallbladder carcinoma cases.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, wall integrity was not a discriminator for adenoma or cholesterol polyp. Several previous studies have reported that wall integrity serves as a risk factor for gallbladder cancer [32,33] but these studies do not report on the relationship between GB wall integrity and the presence of adenoma or cholesterol polyp.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CEUS study has been used to evaluate acute and chronic gallbladder disease, data about its usefulness in the detection of inflammatory complications of acute cholecystitis are sparse [10,[24][25][26][27][28][29][30]. Few reports focus on the diagnostic aid of a CEUS study in the detection of complicated acute cholecystitis such as gangrenous changes or perforation.…”
Section: Discussionmentioning
confidence: 99%